6x+3(4+6x)=2x+2(5x+6)

Simple and best practice solution for 6x+3(4+6x)=2x+2(5x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3(4+6x)=2x+2(5x+6) equation:


Simplifying
6x + 3(4 + 6x) = 2x + 2(5x + 6)
6x + (4 * 3 + 6x * 3) = 2x + 2(5x + 6)
6x + (12 + 18x) = 2x + 2(5x + 6)

Reorder the terms:
12 + 6x + 18x = 2x + 2(5x + 6)

Combine like terms: 6x + 18x = 24x
12 + 24x = 2x + 2(5x + 6)

Reorder the terms:
12 + 24x = 2x + 2(6 + 5x)
12 + 24x = 2x + (6 * 2 + 5x * 2)
12 + 24x = 2x + (12 + 10x)

Reorder the terms:
12 + 24x = 12 + 2x + 10x

Combine like terms: 2x + 10x = 12x
12 + 24x = 12 + 12x

Add '-12' to each side of the equation.
12 + -12 + 24x = 12 + -12 + 12x

Combine like terms: 12 + -12 = 0
0 + 24x = 12 + -12 + 12x
24x = 12 + -12 + 12x

Combine like terms: 12 + -12 = 0
24x = 0 + 12x
24x = 12x

Solving
24x = 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
24x + -12x = 12x + -12x

Combine like terms: 24x + -12x = 12x
12x = 12x + -12x

Combine like terms: 12x + -12x = 0
12x = 0

Divide each side by '12'.
x = 0

Simplifying
x = 0

See similar equations:

| 10-3x=x-2 | | x^2+4x+8y-44=0 | | 6h^2+3=0 | | 6x=9/10 | | 2*x-6=10 | | -301/10x-27 | | 9.40=x/1.65-x | | 5=7-z | | x^2-8x+4x-32=20 | | 10-6(3+10b)= | | 2w+3x= | | 7x+32+6x=9x+3x-62 | | 100=-16t^2+192t+30 | | 3x+140=400 | | 2w=3x | | 44.88=3.4(-3.4n+3) | | 3/4x=3/8(x-5)=1/4 | | 6x^2=20x-6 | | 10(-8+8n)-8= | | 11+10(p-10)=44+5(2p-11) | | 27b+(-4)=-814 | | 600+-4.5y+2y=425 | | 2y^2-7y+8y^2-6y= | | 27(w-972)=297 | | 2x-(18/x)=0 | | -4(3-5x)-4x= | | 63=9(d-84) | | z/8+73=82 | | 7x-3=(3/4(8x-12)) | | 5/x=11.3 | | 2y^2-7y+10=0 | | 9c+10c+2= |

Equations solver categories